Fatal case of necrotising fasciitis due to Vibrio vulnificus in a patient with alcoholic liver disease and diabetes mellitus - Bhat, Prasanna (BMJ Case Rep, 2019)
Vibrio vulnificus is a halophilic Vibrio found globally. They are thought to be normal microbiome in the estuaries along the coasts associated with seawater and seashells. Infection usually results from consumption of raw oysters or shellfish or exposure of broken skin or open wounds to contaminated salt or brackish water. Clinical manifestations range from gastroenteritis to skin and subcutaneous infection and primary sepsis. Pathogen has the ability to cause infections with significant mortality in high-risk populations, including patients with chronic liver disease, immunodeficiency, diabetes mellitus and iron storage disorders. There is often a lack of clinical suspicion in cases due to Vibrio vulnificus leading to delay in treatment and subsequent mortality. Herein we report a case of necrotising fasciitis in a diabetic patient with alcoholic liver disease caused by Vibrio vulnificus which ended fatally.